Integrated Advocacy Approaches In Refusing The Eviction Policy - Daneswara, Ramaditya Rahardian; S Kurnia, Nadya Audina (Jurnal Ilmiah Administrasi Publik, 2018)
This paper aimed to explore the approach of a policy advocacy pursued by residents of Central Jebres RT 02 and 03 RW 25, Jebres Village, Jebres Sub subdistrict, Surakarta City to reject the eviction policy carried out by the Surakarta City Government for the expansion of the Solo Techno Park (STP) land. The method used in this study was a descriptive qualitative namely the handling of their phenomena and providing theoretical interpretation. The findings in the field indicated that the residents of Central Jebres conducted a series of policy advocacy, which among others, such as the formation of a core circle, choosing strategic issues, setting goals and strategies, processing data and packaging information, mobilizing supporters, influencing policy implementer, forming public opinion, creating a basis for movement and the latter monitor the work program. The results of the policy advocacy series conducted by the residents of Central Jebres who had joined the Jebres Demangan citizen alliance had not received positive results.